2014
DOI: 10.1108/jhom-03-2013-0064
|View full text |Cite
|
Sign up to set email alerts
|

Applying lean flows in pathology laboratory remodelling

Abstract: To the best of the authors' knowledge this is the first comprehensive report applying lean flows to pathology laboratory remodelling and one of the few applications of Lean Systems Thinking between departments and between separate health services organisations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 15 publications
2
32
0
1
Order By: Relevance
“…The seven flows of lean manufacturing are the flow of raw material, the flow of work-in-progress, the flow of finished goods, the flow of machines, the flow of operators, the flow of engineering and the flow of information [22]. The mapping of the flows mentioned above allows us to understand how people and materials interact to add value to the product [23].…”
Section: Spaghetti Diagrammentioning
confidence: 99%
“…The seven flows of lean manufacturing are the flow of raw material, the flow of work-in-progress, the flow of finished goods, the flow of machines, the flow of operators, the flow of engineering and the flow of information [22]. The mapping of the flows mentioned above allows us to understand how people and materials interact to add value to the product [23].…”
Section: Spaghetti Diagrammentioning
confidence: 99%
“…Delayed diagnosis, monitoring, and disease management can have adverse effects on patient recovery (Fernandes, Walker, Pricern, Marsden, & Haley, ). Although several solutions have been offered—including the redesign of the ED layout (Hayes et al, ), the decreased use of diagnostic tests (Nugus & Braithwaite, ; Van de Wijngaart, Scherrenburg, Van den, Van Dijk, & Janssens, ), and increased staffing (Jones, Darcy, Souers, & Meier, )—there is no consensus on the most efficient solution.…”
Section: Ed Overcrowdingmentioning
confidence: 99%
“…International literature suggests that, in addition to the over-representation of semiurgent and nonurgent patients, patient flow through an ED is hindered by seven key factors (Crawford et al, 2014). These include delayed: laboratory diagnostics (Hayes, Reed, Fitzgerald, & Watt, 2014); diagnostic radiography (Tambimuttu, Hawley, & Marshall, 2002); patient consultations (Forero, McCarthy, & Hillman, 2011); patient treatment (Pines, Prabhu, Hilton, Hollander, & Datner E., 2010); patient transfer from the ED to a hospital ward (Wong, Wu, Caesar, Abrams, & Morra, 2010) or surgery (Qureshi et al, 2011); and patient discharge from the ED to the community (Handel et al, 2010). These factors, each of which is addressed in turn, collectively reaffirm the interconnectedness between an ED and ancillary departments and services-both within and beyond the hospital.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…43 44 It has been observed that if all relevant healthcare flows have not been considered, this can lead to inappropriate designs and inefficient use of space. 45 PULL -In manufacturing, pull refers to linking production activity to real demand. 30 46 This involves operating the system through pull signals that link internal processes.…”
Section: Introductionmentioning
confidence: 99%